PENGARUH PEMBERIAN SUSU KEDELAI TERHADAP PROFIL LIPID WANITA MENOPAUSE - Rianti; Meti Kusmiati (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Soy milk is the result of extraction from soybeans. Soy milk protein has an amino acid composition similar to cow's milk. Soy milk can be used as a source of nutrition to improve nutritional quality, especially for menopausal women. Menopause is a period when a woman no longer has menstruation because her estrogen hormone production stops. After menopause there are changes in lipid metabolism, which is a risk factor for atherosclerosis. This study aims to determine the effect of soy milk consumption on lipid profiles in menopausal women. The sampling method used was purposive sampling. The number of samples taken was 15 menopausal women. Samples were taken before and after the respondents consumed 200 ml of soy milk every morning and evening for 14 days. The parameters measured include total cholesterol, HDL cholesterol (High Density Lipoprotein), LDL cholesterol (Low Density Lipoprotein) and triglycerides. The statistical results using the Paired T test showed that the significance value for total cholesterol was 0.248, HDL cholesterol 0.000, and LDL cholesterol 0.022 while for triglycerides the significance value was 0.496, So it can be concluded that there is a significant difference in the mean levels of HDL cholesterol and LDL cholesterol but there is no significant difference in total cholesterol and triglyceride levels between before and after giving soy milk to menopausal women.